Electrospun polysulfone/poly(lactic acid) nanoporous fibrous mats for oil removal from water. Issue 5 (July 2019) - Liu, Leigen; Lin, Zhenfeng; Niu, Jiantao; Tian, Dan; He, Jihuan
The study of oil sorbents with high oil sorption capacity is of great significance for oil–water separation, especially for oil spillage on seawater. In this work, we report polysulfone, poly(lactic acid), and polysulfone/poly(lactic acid) nanoporous fibrous mats prepared by one-step electrospinning process used as oil sorbents for oil–water separation. The morphology, porous structure, oleophilicity and hydrophobicity, oil sorption capacity, and oil retention of these nanoporous fibrous mats are investigated in detail. It is noticeable that the motor oil and linseed oil sorption capacity of polysulfone and polysulfone/poly(lactic acid) fibrous mats have little difference, but the motor oil sorption capacity (147.8 g g −1 ) of polysulfone is approximately 2.95 times as much as that (50.1 g g −1 ) of poly(lactic acid). The linseed oil sorption capacity (131.3 g g −1 ) is approximately 3.74 times than that (34.6 g g −1 ) of poly(lactic acid). Besides, they all exhibit quick oil sorption speed and high buoyancy. It is suggested that polysulfone and polysulfone/poly(lactic acid) nanoporous fibrous mats have a better oil sorption capacity than poly(lactic acid) nanoporous fibrous mat, which is contributed to volume expansion, highly micrometer porous structure among fibers, and specific surface area of fiber.